Corporate Social Responsibility Management and Business Strategies in Sustainable Economic Development - Hutsaliuk, Oleksii; Yakusheva, Oksana; Miroshnychenko, Inga; Taburets, Ihor (Dr. Viktor Koval, 2025)
Introduction. Corporate social responsibility (CSR) management is pivotal for the strategic development of the national economy and the sustainability of companies. Considering the intensification of environmental and social issues, companies that integrate the principles of sustainable development into their activities can enhance their image and ensure long-term economic efficiency. Aim and tasks. This study examines the key principles of corporate social responsibility management and their impact on the economic, social, and environmental development of companies. It also examines the role of CSR in sustainable economic development and its significance in establishing a socially responsible business environment. Results. The adoption of CSR principles enhances business positions, as proven by the increase in the number of companies publishing CSR reports from 20% in 2011 to over 90% of S&P 500 companies in 2022. This contributes to positive economic dynamics, with the annual growth of legal entities reaching 8.5% between 2020 and 2023, while the number of private enterprises decreased by 0.2%. The key components of corporate reputational capital included product and service quality (20.2%), management quality (14.9%), citizenship (14.6%), financial success (13.4%), and innovation (13.3%). In 2023, the distribution of companies by CSR type was as follows: large Ukrainian enterprises (67%) and enterprises with foreign capital (18%) were the most common, while multinational corporations accounted for 13%, and medium-sized enterprises accounted for 2%. CSR has a positive impact on company performance, reflected in reputation (93.6%), quality (85.3%), innovation (83%), customer satisfaction (81.7%), productivity (80.4%), and market accessibility (71.3%). Conclusions. CSR management is crucial for sustainable development and promotes responsible economic practices. The analysis of CSR projects of domestic companies in the context of sustainable development and social responsibility has identified key activities of the most socially responsible companies in Ukraine that provide charitable assistance to the population (74%), support medical services (54%), and organise leisure activities and resettlement (47%). The implementation of corporate social responsibility through innovations, social programs, and environmental initiatives not only adds value to businesses but also fosters favourable changes in the community and the environment.